2022
DOI: 10.1111/hex.13550
|View full text |Cite
|
Sign up to set email alerts
|

Using cocreated visually informed community mental health education in low‐ and middle‐income countries: A case study of youth substance misuse in Assam, India

Abstract: Introduction: Our aim is to evaluate the visually informed community mental health education materials cocreated in our research on youth substance misuse in Assam, India, and to reflect on what we might learn for similar initiatives in low-and middleincome countries.Methods: Materials consist of: (i) images participants brought to the interview; (ii) 30 posters cocreated by participants to convey key messages from their interview; (iii) six short films on the implications of addiction, and (iv) an animation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A number of health interventions using social media have been co-designed with young people and have utilised platforms such as Facebook Messenger and Instagram [ 39 , 40 , 41 , 42 ]. Other promotion strategies within academic research have involved collaboration with film makers to develop short educational films [ 43 , 44 ]. For example, the short films for the “What’s Up with Everyone” project were disseminated via YouTube [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of health interventions using social media have been co-designed with young people and have utilised platforms such as Facebook Messenger and Instagram [ 39 , 40 , 41 , 42 ]. Other promotion strategies within academic research have involved collaboration with film makers to develop short educational films [ 43 , 44 ]. For example, the short films for the “What’s Up with Everyone” project were disseminated via YouTube [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of these potential policy initiatives, we have cocreated a visually informed community education package around our model 49 . Early piloting has been conducted in Assam with high school students, the general public, postgraduate mental health trainees and women in rural and semirural districts.…”
Section: Discussionmentioning
confidence: 99%
“…The key implications of this research for policy development in In support of these potential policy initiatives, we have cocreated a visually informed community education package around our model. 49 Early piloting has been conducted in Assam with high school students, the general public, postgraduate mental health trainees and women in rural and semirural districts. This demonstrated that the education package was successful in promoting young people's voice with regard to SUD prevention and recovery, increasing awareness of their needs and has the potential for stigma reduction.…”
Section: Discussionmentioning
confidence: 99%